The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/aian.aian_466_17
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcome in convulsive status epilepticus in adults: An ambispective study from central India

Abstract: Background:The determinants of the outcome in adult convulsive status epilepticus(CSE), also the implication of the value of mean arterial blood pressure (MAP), and random blood sugar at admission on the outcome are not clear.Objectives:The objective of this study is to look for the determinants of unfavorable outcome in CSE.Materials and Methods:Ambispectively gathered data from 55 patients, treated consecutively with identical protocol during January 2010–December 2016, were analyzed. The demographic and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The most common type of seizure at presentation in our study was GTCS, while patients with UTCS had the most unfavourable outcome [6]. This is in contrast to the ambispective study conducted by Dani et al, who reported GTCS as a determinant for unfavourable outcomes [3]. A low GCS score at the time of the first assessment (GCS of <=12 in our study) was identified as a significant independent risk factor for an unfavourable outcome.…”
Section: Clinical Variables Versus Outcomescontrasting
confidence: 80%
See 3 more Smart Citations
“…The most common type of seizure at presentation in our study was GTCS, while patients with UTCS had the most unfavourable outcome [6]. This is in contrast to the ambispective study conducted by Dani et al, who reported GTCS as a determinant for unfavourable outcomes [3]. A low GCS score at the time of the first assessment (GCS of <=12 in our study) was identified as a significant independent risk factor for an unfavourable outcome.…”
Section: Clinical Variables Versus Outcomescontrasting
confidence: 80%
“…Older age at presentation was associated with poor outcomes, and a similar association has been shown in past studies. The cutoff of age with poor outcomes in our study was 36 years; however, the association was not significant [2,3,[11][12][13][14]. While some studies have shown female gender being associated with unfavourable outcomes, the gender of our study patients did not show any significant correlation, although male patients were more in number than female patients [15,16].…”
Section: Demographic Variables Versus Outcomescontrasting
confidence: 79%
See 2 more Smart Citations
“…Mortality from GCSE varies between 3 and 39%. [1][2][3][4][5][6][7] As such, GCSE often requires hospital admission and results in major health resource utilization and hospital costs. 8 Characterizing hospitalizations after GCSE is an essential step in curbing fatality rates and healthcare expenditures related to GCSE.…”
Section: Introductionmentioning
confidence: 99%